Study of solar powered electric vehicles charging station in Kathmandu valley-A case study of sundar yatayat - Adhikari, Surya; Pal, Bikash Kumar (Journal of Innovations in Engineering Education, 2022)
In this paper, a feasibility study is done about the techno-economical aspect of installing the solar PV system for charging electric vehicles. Public electric vehicles operated by company, Sundar Yatayat Pvt. Ltd. are taken into consideration for data collection and feasibility test.The company operates four vehicles currently, two buses of length 10.5m and 8.5m and two vans of length 6m which runs in ring-road of Kathmandu valley. A survey is conducted regarding the types of vehicles operated, charging pattern of the vehicles, number of units consumed to charge the vehicles, charging location, annual income as well as its operation and maintenance costs, internal rate of return (IRR) and payback period are used for the feasibility of the use of solar PV energy for charging the vehicles. There are four vehicles in operation at present, so the comparison is done between charging the vehicles through various percentage share of solar PV system to the current charging units i.e., 100%, 80% and 50% share of solar PV system. In all three cases, the Levelized Cost of electricity is calculated and the vehicle operating routes are studied inside Kathmandu valley. Finally, the optimal and feasible solution for solar-based charging and the optimal route for profit maximization is proposed in this paper. Best feasible solution is found if the vehicles are charged through 80% share of solar PV and other through grid with discounted payback period of 5.03 years and LCOE of Rs. 5.72 per kWh